فعالية الذات الأكاديمية وعلاقتها بدافع الإنجاز الأكاديمي لدى طلبة التعليم المفتوح دراسة ميدانية على عينة من طلبة رياض الأطفال في جامعة تشرين (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
هدفت الدراسة إلى التعرف على طبيعة العلاقة الارتباطية بين فعالية الذات الأكاديمية، ودافع الإنجاز الأكاديمي لدى عينة من طلبة رياض الأطفال في كلية التربية بجامعة تشرين بلغت (282) من السنوات الدراسية الأربع، إلى جانب الكشف عن الفروق في مستوى فعالية الذات تبعاً للتخصص الدراسي في المرحلة الثانوية، والتقدم في السنوات الدراسية، وذلك باستخدام مقياس صورة فعالية الذات في التعلم إعداد باري زميرمان وأناستاسيا كيتسانتاس(Barry J.Zimmerman&Anastasia Kitsantas)، ومقياس دافع الإنجاز الأكاديمي من إعداد (جديد، 2009). وبينت النتائج وجود علاقة ارتباطية إيجابية بينهما، كما بينت عدم وجود فروق في فعالية الذات الأكاديمية تبعاً للتخصص في المرحلة الثانوية، في حين وجدت فروق فيها تبعاً للسنة الدراسية الأعلى حيث تكون في أدنى مستوياتها في السنة الأولى ثم تواصل ارتفاعها في السنوات اللاحقة.The study aimed to realizing the correlative relation between academic self-efficiency and the motivation for academic per for mance of a sample of kindergarten students at the faculty of education at Tishreen University. The sample included (282) students from four academic years and discovered the differences at the level of self–efficiency according to the educational specialization at the secondary stage and according to progressing in the years of education. By using the scale of the self-efficiency form in learning by (Barry j. Zimmerman & Anastasia Kitsantas) and the scale of academic performance motivation by (JDID,2009). The results indicated positive relationship between them and there were no differences at the level of self–efficiency according to specialization at the secondary stage. However, there were differences according to the progress of the years of education at their lowest levels at the first year then they kept increasing throughout the following years.